A solitary presentation of panniculitis in a patient with a history of breast cancer - Garcia-Hernandez, Irean (Ann Med Surg (Lond), 2018)
INTRODUCTION: Panniculits presents as an inflammation of the subcutaneous adipose tissue of the skin. In breast, panniculitis is very rare and is usually a manifestation of underlying inflammatory conditions. The typical presentation is palpable tender nodules, which in cases of breast panniculitis, triggers an extensive work up to exclude a malignancy. Herein we present a case of septal and lobar panniculitis in a female with clinical history of invasive ductal carcinoma. PRESENTATION OF THE CASE: A 52-year old female with past medical history of invasive breast carcinoma 5 years prior to the presentation. The patient's chief complaint was a 1-year history of a subcutaneous nodular lesion on her left breast. A core biopsy of the firm nodule showed marked inflammation of the breast. A second skin biopsy showed an abundant chronic inflammatory infiltrate, with lymphocytic vasculitis and neuritis, suggestive of an underlying autoimmune process. DISCUSSION: Subcutaneous panniculitis with or without vasculitis is a rare condition when presenting in the breast. Panniculitis can mimic malignancy and thus, it is important to differentially diagnose it from breast carcinoma. Histologically, it is classified in lobular and septal lymphocytic panniculitis depending on specific diagnostic characteristics. CONCLUSION: Panniculitis of the breast is a rare condition that needs to be included in the differential diagnosis of subcutaneous breast masses. In all cases, but specifically in females with history of breast cancer, panniculitis still should be thought of as a possibility, and imaging as well as other diagnostic techniques can aid in making the correct diagnosis.